PARALLEL COMPUTING IN ECONOMICS - AN OVERVIEW OF THE SOFTWARE FRAMEWORKS - Bogdan OANCEA (Challenges of the Knowledge Society)
This paper discusses problems related to parallel computing applied in economics. It introduces the paradigms of parallel computing and emphasizes the new trends in this field - a combination between GPU computing, multicore computing and distributed computing. It also gives examples of problems arising from economics where these parallel methods can be used to speed up the computations.